Computed Tomographic Diagnosis of Myocardial Fat Deposits in Sarcoidosis. Issue 4 (July 2015) - Saremi, Farhood; Saremi, Arvin; Hassani, Cameron; Cen, Steven; Lin, Leah; Ng, Brian; Shahriarian, Shahriar
<x xml:space="preserve">Abstract</x> Objective Fat deposits in the left ventricle (LV) myocardium are uncommon and usually indicate scar due to chronic myocardial infarction. The purpose of this study was to determine the incidence of fatty lesions in the LV of patients with sarcoidosis. Materials and Methods Review of noncontrast computed tomographic images (2-mm thickness) in 133 patients with documented extracardiac sarcoidosis (age, 35–82 years, 55 ± 10 years, 67% female) with no history of significant coronary artery disease (clinical and coronary calcium) was performed. A control group included noncontrast computed tomographies with no coronary calcium in 133 patients with age/sex (59 ± 6 years, 73% female) similar to the sarcoid target group. Locations and morphology (linear vs bulky) of fat deposits (−30 to −180 Hounsfield units) and relevant intrathoracic findings were recorded. Results We found 35 fat deposits in 19 (14.3%) of sarcoid patients (target group: age, 59 ± 7 years, 78% female). Lesions were mainly at the LV apical level (n = 14). In the control group, 15 lesions in 13 (9.7%) patients were found. Numbers of fatty lesions in sarcoid targets were significantly higher than those in the control group (P = 0.015). The number of bulky lesions was significantly higher in sarcoid (n = 9) than in control (n = 1; P < 0.05). No significant difference was found for the rate of linear lesions. Interstitial lung disease was seen in 9 and enlarged lymph nodes in 9 of the sarcoid target group. There was no significant correlation between the severity of interstitial lung disease and the number of fatty lesions. Conclusions Sarcoid patients demonstrate a higher chance of having LV fat deposits with a characteristic bulky morphology.